Strontium isotope analysis on cremated human remains from Stonehenge support links with west Wales - Snoeck, C; Pouncett, J; Claeys, P; Goderis, S; Mattielli, N; Parker Pearson, M; Willis, C; Zazzo, A; Lee-Thorp, J; Schulting, R (Nature Publishing Group, 2018)
Cremated human remains from Stonehenge provide direct evidence on the life of those few select individuals buried at this iconic Neolithic monument. The practice of cremation has, however, precluded the application of strontium isotope analysis of tooth enamel as the standard chemical approach to study their origin. New developments in strontium isotopic analysis of cremated bone reveal that at least 10 of the 25 cremated individuals analysed did not spend their lives on the Wessex chalk on which the monument is found. Combined with the archaeological evidence, we suggest that their most plausible origin lies in west Wales, the source of the bluestones erected in the early stage of the monument's construction. These results emphasise the importance of inter-regional connections involving the movement of both materials and people in the construction and use of Stonehenge.